(untitled) (Eurasian Journal of Philology Science and Education, 2026)
In the process of interpersonal communication unfolding in various speech situations, one of the types of speech actions manifested is communicative pressure or verbal pressure. In the process of interpersonal communication, certain instances of the addresser’s utterances aimed at exerting aggressive influence on the addressee may be regarded as a linguistic offence, as they involve actions that restrict the addressee’s personal freedom or force them to engage in actions they do not wish to perform. This highlights the importance of investigating the linguistic markers and language means of communicative pressure for both the theory and practice of forensic linguistics. The article aims to identify the key linguistic features, speech strategies and tactics of communicative pressure as a form of linguistic offence through a linguistic analysis of specific empirical material. In this regard, a linguistic analysis was conducted based on a specific instance of communicative pressure – a written statement exchanged between divorced spouses and a video recording of their conversation. Communicative pressure is examined as a speech act designed to inflict harm on the interests of the addressee or the opposing party, as well as to exert influence that contradicts their rights. The study employs theoretical concepts from speech act theory, along with pragmalinguistic, syntactic, stylistic and orthographic methods of analysis. As a result, based on a written note and a video recording of a conversation between divorced spouses, the linguistic markers and language means characteristic of communicative pressure realized under the condition of restricting the addressee’s (listener’s) freedom were identified, and the linguistic tactics were systematized. Keywords: communicative pressure, verbal means, speech strategies, linguistic tactics, linguistic offence.